Bay’ al-Salam and Istithne: implementation and challenges - Mohamad, Azhar; Sifat, Imtiaz Mohammad; Hasmawati, Anisza; S.M. Qatei, Mo'min (IIUM Press, 2017)
The raison d’être in Bay’ al-Salam and IstithnÉ’ is to help the ummah in answering the basic question in economy – “How do we allocate resources from the rich to the poor?” In Bay’ al-Salam, the rich buyer pays the poor farmer (seller), in full, while the poor farmer agrees to deliver the crops in the future. Much as the society would want to help the poor farmer, the seller is faced with counterparty risks – there are chances that for some reasons, the farmer is not able to deliver the crops to the seller on the agreed date. Islamic financial institutions in Malaysia, although they perfectly understand the concept of “al-GhurmÊ bil-ghunmÊ” (without risk, there will be no gain), still consider counterparty risks in Bay’ al-Salam arrangements to be too big to chew. Similarly, IstithnÉ’ is a unique type of sale contract that is used in the manufacturing or construction sectors where the sale of a commodity is transacted before the commodity comes into existence. The benefit of IstithnÉ’ is the special flexibility of this mechanism such that the full price need not be paid on the spot, at the time of the contract being made. IstithnÉ’ arises in society due to the specific needs of the Muslim population. The growing Malaysian economy in 2014, in which 15.2% comes from manufacturing and construction sectors, as well as continuous support by the Bank Negara Malayisa (BNM) to strengthen the Islamic Financial Institutions (IFIs) in the country are the supporting factors to encourage the application of IstithnÉ’ financing in Malaysia. However, data from the BNM showed that IstithnÉ’ financing is still scarce. Athough IstithnÉ’ contract is used currently by some businesses, it doesn’t enjoy great popularity due to several factors, mainly because of its risks and regulations. This book – Bay’ al-Salam and IstithnÉ’: Applications, Risks, and Related Issues from the Malaysian Perspective – discusses the inherent risks, particularly the counterparty risks associated with the contract and its potential implementation despite the constraints. With regards to IstithnÉ’ this book recommends to further develop in Malaysia because it holds great potential, and it needs a movement from all elements in the financial system, including the Islamic banks’ promotion of IstithnÉ’ products, to bring about customer demand for it in the market, as well as to bring about supportive regulation from the BNM. It is hoped that, with this discussion on Bay’ al-Salam and the application of IstithnÉ’ financing in Malaysia, our society will be able to provide more answers to the basic question in the economy of how to help the poor and needy.